On C1-robust transitivity of volume-preserving flows - Bessa, Mário (2008)
We prove that a divergence-free and C1-robustly transitive vector field has no singularities. Moreover, if the vector field is smooth enough then the linear Poincaré flow associated to it admits a dominated splitting over M.